Cross-sectoral collaboration in mental health services: Identifying the role of mental health care teams in the community - Osi Kusuma Sari; Subandi Subandi; Carla Raymondalexas Marchira (Journal of Community Empowerment for Health, 2021)
Strengthening integrated and community-based mental health services is essentially needed to address the treatment gap and provide effective services that can be accessed by all groups. To realize this goal, the cross-sectoral involvement that is part of the Tim Pembina, Pengarah, dan Pelaksana Kesehatan Jiwa Masyarakat (TPKJM) is at the forefront because it has direct access to mental disorders cases in their region. This article aims to identify the role of each member of TPKJM in pursuing mental health services. Participants involved in each stage of data collection were members of TPKJM at the sub-district and village levels. The data were collected using three methods: surveys, focus group discussions, and interviews. The collected data were analyzed using an inductive thematic analysis approach to obtain a description of the role of each member of TPKJM within the case handling flow model. Five role themes were identified, including: (a) setting regulations and planning; (b) community clinical services; (c) psychoeducation; (d) safeguarding emergency cases; and (e) administrative advocacy. Regulations regarding the clarity of roles and handling flow are recommended.